Correlation between diameter of esophageal varices and early rebleeding following endoscopic variceal ligation: a multicenter retrospective study based on artificial intelligence-based endoscopic virtual rule - Cao, Chuankun; Jin, Jing; Cai, Rui; Chu, Yuan; Wu, Kai; Wang, Zuo; Xiao, Ting; Zhang, Heng; Huang, Hongfei; Liu, Heng; Zhang, Qianqian; Mei, Xuecan; et al. (Frontiers in Medicine, 2024)
Background and objective Bleeding following endoscopic variceal ligation (EVL) may occur as a result of numerous factors, including a diameter of esophageal varices (EV) that is too large to be completely ligated. The present study aimed to develop an artificial intelligence-based endoscopic virtual ruler (EVR) to measure the diameter of EV with a view to finding more suitable cases for EVL. Methods The present study was a multicenter retrospective study that included a total of 1,062 EVLs in 727 patients with liver cirrhosis with EV, who underwent EVL from April 2016 to March 2023. Patients were divided into early rebleeding (n = 80) and non-rebleeding groups (n = 982) according to whether postoperative bleeding occurred at 6 weeks. The characteristics of patient baseline data, the status of rebleeding at 6 weeks after surgery and the survival status at 6 weeks after rebleeding were analyzed. Results The early rebleeding rate following 1,062 EVL procedures was 7.5%, and the mortality rate at 6 weeks after bleeding was 16.5%. Results of the one-way binary logistic regression analysis demonstrated that the risk factors for early rebleeding following EVL included: high TB (P = 0.009), low Alb (P = 0.001), high PT (P = 0.004), PVT (P = 0.026), HCC (P = 0.018), high Child-Pugh score (P < 0.001), Child-Pugh grade C(P < 0.001), high MELD score(P = 0.004), Japanese variceal grade F3 (P < 0.001), diameter of EV (P < 0.001), and number of ligature rings (P = 0.029). Results of the multifactorial binary logistic regression analysis demonstrated that Child-Pugh grade C (P = 0.007), Japanese variceal grade F3 (P = 0.009), and diameter of EV (P < 0.001) may exhibit potential in predicting early rebleeding following EVL. ROC analysis demonstrated that the area under curve (AUC) for EV diameter was 0.848, and the AUC for Japanese variceal grade was 0.635, which was statistically significant (P < 0.001). Thus, results of the present study demonstrated that EV diameter was more optimal in predicting early rebleeding following EVL than Japanese variceal grade criteria. The cut-off value of EV diameter was calculated to be 1.35 cm (sensitivity, 70.0%; specificity, 89.2%). Conclusion If the diameter of EV is ≥1.4 cm, there may be a high risk of early rebleeding following EVL surgery; thus, we recommend caution with EVL.